Wybrane aspekty łódzkiego rynku pracy - Zajdel, Mirosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The process of socio-economic transformation in Poland generates many changes both of local and national character. In this situation, the role of the Lodz labour market undergoes a constant evolution.This paper concerns the analysis of the selected aspects of the labour market of Lodz. The main goal is to present various problems concerning the condition and the structure of employment, unemployment and vacancies in Lodz. The characteristic features of these problems include among others, some drop in the number of persons employed in the local economy and a diminishing share of employees in the industrial sector accompanied by a growing share of persons engaged in services, as well as growing employment in the private sector. Moreover, the following research problems have been distinguished: the level and structure of unemployment, the selected problems of groups concerning the local labour market, the inflow and outflow from unemployment.The report is based on statistical data and information provided by the Provincial Statistical Office in Lodz and the Provincial Labour Office, as well as by the Central Statistical Office in Warszawa. The data were helpful when analyzing the labour market of Lodz. It should be noted also that a number of different issues connected with the Lodz local labour market are open. Hence, it would seem advisable to continue the research in this field. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 75-84